2020
DOI: 10.2196/21704
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and Expectations of Health Care Professionals Toward App-Based Therapy in Patients with Osteoarthritis of the Hip or Knee: Questionnaire Study

Abstract: Background The use of mobile health (mHealth) apps is becoming increasingly widespread. However, little is known about the attitudes, expectations, and basic acceptance of health care professionals toward such treatment options. As physical activity and behavior modification are crucial in osteoarthritis management, app-based therapy could be particularly useful for the self-management of this condition. Objective The objective of the study was to deter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 115 publications
3
8
1
Order By: Relevance
“…Furthermore, respondents who had high digital literacy were 1.7 times more likely to have a good attitude towards TR compared to those who have low digital literacy (AOR: 1.743(95%CI: 1.028, 2.954). This nding is consistent with the study nding in Ethiopia (26) (27), Sweden(18), Saudi Arabia (23), Pakistan (12), German (19) and Libya (21) (28).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Furthermore, respondents who had high digital literacy were 1.7 times more likely to have a good attitude towards TR compared to those who have low digital literacy (AOR: 1.743(95%CI: 1.028, 2.954). This nding is consistent with the study nding in Ethiopia (26) (27), Sweden(18), Saudi Arabia (23), Pakistan (12), German (19) and Libya (21) (28).…”
Section: Discussionsupporting
confidence: 93%
“…Participants who own smartphones were 1.9 times more likely to have a good attitude towards telerehabilitation than those who didn't have smartphones. This nding was consistent with the study conducted in Ethiopia(26) and Germany (19). Furthermore, respondents who had high digital literacy were 1.7 times more likely to have a good attitude towards TR compared to those who have low digital literacy (AOR: 1.743(95%CI: 1.028, 2.954).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…While the study identified the usefulness of mobile apps for skin conditions along with user expectations, the study was very specific to apps for detecting melanoma. Another recent study conducted with healthcare professionals to determine their expectations with mHealth apps [32] has shown expectations of data protection and privacy with a high acceptance of app-based therapies. However, just like the others, the study was still limited to one specific domain.…”
Section: Introductionmentioning
confidence: 99%
“…Digital therapeutics have emerged as an option to provide access to exercise therapy and multidisciplinary rehabilitation for patients with musculoskeletal pain conditions such as osteoarthritis and back pain [8][9][10]. Even though a recent survey among health professionals indicated widespread support of use of mobile health technologies in osteoarthritis treatment [11], a primary concern with using digital therapeutics for home-based exercise is the lack of supervision by health care professionals.…”
Section: Introductionmentioning
confidence: 99%